(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Malaria remains a major public health concern in Nigeria, which accounts for 27% of global malaria cases and 32% of global malaria deaths in 2022. Despite intensified control efforts, the disease continues to impact communities such as Oluyole Local Government Area (LGA), Ibadan, where environmental and socio-economic factors favor persistent transmission. This study assessed the knowledge, attitudes, and perceptions (KAP) of residents toward malaria infection to identify community-level gaps that may hinder effective control. A cross-sectional survey was conducted among inhabitants of Oluyole LGA using a structured questionnaire. Findings revealed that 85.0% of respondents correctly identified mosquito bites as the primary mode of transmission, while 72.0% recognized fever as a major symptom. However, 18.0% still associated malaria with incorrect causes such as exposure to sunlight or consumption of certain foods. Attitudes toward treatment were largely positive: 60.0% reported they would seek medical care within 24 hours of symptom onset, whereas 15.0% would delay treatment for more than three days. Trust in conventional medicine was high, with 75.0% expressing confidence in prescribed antimalarial drugs, compared with 25.0% who still preferred herbal remedies. Regarding preventive practices, 70.0% expressed favorable attitudes toward measures such as indoor residual spraying and mosquito coil use, although regular use of insecticide-treated nets remained suboptimal. The study demonstrates relatively high awareness and positive attitudes toward malaria prevention and treatment, though misconceptions and inconsistent preventive behaviors persist. Strengthening community-based sensitization, improving access to preventive tools, and addressing traditional treatment preferences will support Nigeria’s broader malaria elimination efforts.